2014
DOI: 10.1118/1.4892176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dosimeter type for commissioning small photon beams on calculated dose distribution in stereotactic radiosurgery

Abstract: The results of this study showed that all of the studied detectors produced similar commissioned data sets for the TPS dose calculations. However, this result only validated the dose distribution calculation in the TPS and could not be used to assess the dose delivery to the target in which the TFS data were used to calculate the monitor units (the TFS data were not used in the TPS dose distribution calculation). Therefore, this study could not be used to determine the most accurate detector commissioning data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…The microLion has been discontinued by manufacturer and is not available commercially. For the Gafchromic EBT2/3 films, proper precautions and experience is needed for achieve comparable data (59)(60)(61). User should also evaluate the criterion for correction-less dosimetry if there is any doubt as discussed by Kamio and Bouchard (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microLion has been discontinued by manufacturer and is not available commercially. For the Gafchromic EBT2/3 films, proper precautions and experience is needed for achieve comparable data (59)(60)(61). User should also evaluate the criterion for correction-less dosimetry if there is any doubt as discussed by Kamio and Bouchard (57).…”
Section: Discussionmentioning
confidence: 99%
“…The notation f ref denotes the conventional reference field in dosimetry protocols for which the calibration coefficient of an ionization chamber in terms of absorbed dose to water is provided by a standard laboratory and Q is the beam quality of f ref . The f msr is the machinespecific-reference field, N D,w is the chamber specific calibration coefficient in terms of absorbed dose to water for 60 Co, and k Q,Qo is chamber specific beam quality calibration factor. Unfortunately the last term in Eq 1 the k values are not readily available and there is some variability in the literature.…”
Section: Iaea Approachmentioning
confidence: 99%
“…The calculation grid size was set to 2 mm (see Fig 2E–2G ). Note that García-Garduño et al [ 2 ] previously showed that the gamma index criteria were not sensitive to the calculation grid size for circular cone-based radiosurgery.…”
Section: Methodsmentioning
confidence: 98%
“…Problems related with the dosimetry of small radiotherapy photon beams have been extensively discussed in the literature [ 1 ]. In response these problems, many detectors have been manufactured specifically for the dosimetry of small photon beams with certain advantages and disadvantages [ 2 ]. In particular, silicon-diode-based detectors have been commonly used because of their relatively small volumes and high sensitivity to ionizing radiation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation